An a Priori Estimate for a Scalar Transmission Problem of the Laplacian in R3 (Global Journal of Science Frontier Research, 2016)
In this work, we present an a priori estimate for a scalar transmission problem of the Laplacian with parameter in R 3 . The solution at infinity is described in the family of weighted Sobolev spaces.
Keywords: scalar transmission problem; laplacian; a priori estimate